Relocation, high‐latitude warming and host genetic identity shape the foliar fungal microbiome of poplars. Issue 1 (31st December 2014) - Bálint, Miklós; Bartha, László; O'Hara, Robert B.; Olson, Matthew S.; Otte, Jürgen; Pfenninger, Markus; Robertson, Amanda L.; Tiffin, Peter; Schmitt, Imke
Abstract Micro‐organisms associated with plants and animals affect host fitness, shape community structure and influence ecosystem properties. Climate change is expected to influence microbial communities, but their reactions are not well understood. Host‐associated micro‐organisms are influenced by the climate reactions of their hosts, which may undergo range shifts due to climatic niche tracking, or may be actively relocated to mitigate the effects of climate change. We used a common‐garden experiment and rDNA metabarcoding to examine the effect of host relocation and high‐latitude warming on the complex fungal endophytic microbiome associated with leaves of an ecologically dominant boreal forest tree (Populus balsamifera L.). We also considered the potential effects of poplar genetic identity in defining the reactions of the microbiome to the treatments. The relocation of hosts to the north increased the diversity of the microbiome and influenced its structure, with results indicating enemy release from plausible pathogens. High‐latitude warming decreased microbiome diversity in comparison with natural northern conditions. The warming also caused structural changes, which made the fungal communities distinct in comparison with both low‐latitude and high‐latitude natural communities, and increased the abundance of plausible pathogens. The reactions of the microbiome to relocation and warming were strongly dependent on host genetic identity. This suggests that climate change effects on host–microbiome systems may be mediated by the interaction of environmental factors and the population genetic processes of the hosts.